Comparison of Functional Outcome After 2 Weeks Immobilization Versus No Immobilization After Reduction of Acute Shoulder Dislocation - Ullah, Mishkat; Amin, Suhail; Iqbal, Musawir; Tufail, Muhammad; Siddique, Asnaf; Khalid, .; Rafique, Faisal (Biological and Clinical Sciences Research Journal, 2025)
Acute anterior shoulder dislocation is an injury that happens mostly in people who are active and younger. After reducing the dislocation, immobilizing the joint is an accepted treatment, but the ideal time for removal is argued, since some studies report that early movement may help you recover faster. Objective: To analyze whether resting the shoulder is better than moving it after a closed reduction for first-time anterior shoulder dislocation. Methods: The study was carried out in the Orthopedic Surgery Department of CMH Rawalpindi between 15 June 2024 to 14 Feb 2025. The study grouped sixty patients into two groups. Group A was repaired and then confined to bed for two weeks; Group B was not immobilized and was encouraged to move as soon as possible. Constant-Murley and DASH scores were used to measure function at 2, 6, and 12 weeks after reducing the fracture. Results: Group B consistently had better mean scores for Constant-Murley and DASH at 6 and 12 weeks, with p < 0.01 (statistical significance). No differences in rates of redislocation were noticed between the groups. Conclusion: Early mobilization without immobilization after anterior shoulder dislocation results in superior short-term functional outcomes and may be a viable alternative to traditional immobilization.